The Novel and the Hidden information ( Jacob’s Disappointment and the sun’s other face ) - Ali Hasan Hthelee ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
A good novel has the ability to hide its information under the words hills. It passes the message smartly and lightly . It engages openly with the action while it deeply engages with another task or action. We can simply say that this type of novels is near to the delusion than to writing as it is said in books of eloquence . In this research we try to seek the hidden information in these two novels ( Jacob’s Disappointment written by Sadoon Al – Badani and the sun’s other face by Tahsen Ali Kradi )